Parametric study of a thin piezoelectric cantilever for energy harvesting applications. (19th May 2018) - Hoang, T.; Poulin-Vittrant, G.; Ferin, G.; Levassort, F.; Bantignies, C.; Nguyen-Dinh, A.; Bavencoffe, M.
ABSTRACT: Nowadays, bimorph piezoelectric cantilevers are commonly used in ambient vibrational piezoelectric energy harvesting. They are constituted of two thin layers of piezoelectric material separated by an inner shim material. To help the design process of these energy harvesting devices, analytical and numerical models have been developed. This work presents a parametric study to determine the effective coefficients of a thinned piezoelectric layer. To this aim, a one-dimensional analytical model and a three-dimensional finite element (FE) model are investigated: a thinned layer of PZT material in free mechanical boundary conditions is considered. The one-dimensional analytical admittance model allows the determination of the elastic, dielectric and piezoelectric coefficients of the piezoelectric layer. Then, in order to determine the influence of all coefficients of the compliance, dielectric and piezoelectric tensors, a FE model is investigated.